Teacher certification education: A review competence of Indonesian language and literature - SYAMSURI, A.S; ISHAQ, I.; CHAERUMAN, U.A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objectives of the present research were to assess the efficacy of TPE hybrid learning approaches in boosting the competencies of Indonesian language and literature teachers in Indonesia, to determine the lessons that Indonesia can draw from both developing and industrialized countries to heighten the quality of their Indonesian language and literature instructors exploring the challenges associated with TPE hybrid learning techniques among Indonesian language and literacy educators. The study adopted a qualitative descriptive research design that involved a group interview with four conveniently sampled Bahasa Indonesia language and literature teachers. RESUMEN Los objetivos de la presente investigación fueron evaluar la eficacia de los enfoques de aprendizaje híbrido de TPE para aumentar las competencias de los profesores de lengua y literatura indonesias en Indonesia, para determinar las lecciones que Indonesia puede extraer de los países en desarrollo e industrializados y aumentar la calidad de sus instructores de lengua y literatura explorarando los desafíos asociados con las técnicas de aprendizaje híbrido de TPE entre los educadores de lengua y literatura de Indonesia. El estudio adoptó un diseño de investigación descriptivo cualitativo que incluyó una entrevista grupal con cuatro maestros de lengua y literatura de Bahasa Indonesia convenientemente incluidos en la muestra.